Synthesis of sodalite-natural dolomite as novel bifunctional catalyst for biodiesel production: Experimental study of performance and emissions on diesel engine - Hamid, Abdul; Fatah, Misbakhul; Rahmawati, Zeni; Saiful, S.; Purbaningtias, Tri Esti; Jakfar, Amin (Center of Biomass & Renewable Energy (CBIORE), 2025)
The development of catalysts derived from natural minerals was investigated in this study for biodiesel production due to their high catalytic activity, abundant availability, low production cost, and environmentally friendly. Biodiesel was produced from Calophyllum Inophyllum (CI) oil using bifunctional catalyst synthesized from natural dolomite and sodalite. In addition, an experimental study was conducted to evaluate the performance and emission characteristics of the produced biodiesel in a diesel engine. The natural dolomite catalyst contains a high composition of CaO-MgO, while sodalite, consisting of Si and Al precursors, was synthesized from natural kaolin. The bifunctional catalysts were synthesized via wet impregnation method with varying loadings of natural dolomite (5, 10, 15, 20, and 25 wt%). FTIR, XRD, SEM-EDX, and N2 adsorption-desorption analyses were employed to characterize the physicochemical properties of the catalysts. The optimum biodiesel yield of 94.14 % was obtained at dolomite loading of 25 wt%. Engine performance tests revealed that the B10 fuel blend produced maximum power and torque of 1.252 kW and 69.151 N.m, respectively, at 1250 rpm. While the optimum specific fuel consumption was obtained at 0.0004 Kg.HP/h at 1250 rpm for all fuel blends.The lowest CO emission was recorded for the B40 fuel blend at 414 ppm, while the lowest NO and NOx emissions were observed for the D100 fuel at 88 and 86 ppm, respectively.